Extração e caracterização físico-químicas e reológicas de amido de milho (Zea Mays L.) pipoca crioulo - César, Ana Luiza Trovo Marques de Souza (2021)
Starch, coming mainly from cereals such as corn, has been used by the food industry as a caloric ingredient and also as an enhancer of physicochemical properties. It is used to change or control characteristics such as texture, appearance, moisture, consistency and stability, which directly impact the quality and sensory characteristics of the products that contain it. Thus, the objective of this work was to extract corn starch from Creole popcorn (Zea Mays L.) for its use, analyzing its physical chemical and its rheological characteristics with a view to its use in the manufacture of processed foods. For this, analyzes of the proximal composition, thermal properties and rheological behavior were carried out. Analyzes of yield, pH, color, sizes and shapes of the granules verified by SEM (Scanning Electron Microscopy), thermo gravimetric (DTA/TG), FTIR, DRX and rheological analyzes such as flow curves, scanning of temperature, strain, frequency, temperature and time scan. The extraction yield of starch from colored popcorn (Zea Mays L.) corn was 6.3%. Its characteristics are common to many starches, but also different, such as the low acidity (pH 5,11±0,01) that favors its use to increase viscosity in other industrialized products. The sizes and shapes of the granules verified by SEM justify their viscoelastic behavior and rheological characteristics. Likewise, they may have contributed to their loss of mass (85%) along with their protein and lipid levels(5,10±0,15; 2,05±0,07).. The lipid concentration was also decisive in the gelatinization of the starch in the present study. Infrared spectroscopy confirmed that colored popcorn starch (Zea Mays L.) typically behaved like other starches, as well as it'scrystalline. Thus, the studied starch represents another alternative and also a technological innovation as it represents a technological advance, adding nutritional value to the food that contains it. In this sense, the present work is not only justified, but also guarantees great perspectives for science and the food industry